Distribution of Negative J·E′ in the Inflow Edge of the Inner Electron Diffusion Region During Tail Magnetic Reconnection: Simulations Vs. Observations. Issue 11 (31st May 2022) - Xiong, Q. Y.; Huang, S. Y.; Zhou, M.; Yuan, Z. G.; Deng, X. H.; Jiang, K.; Wei, Y. Y.; Xu, S. B.; Zhang, J.; Lin, R. T.; Yu, L.
Abstract: Magnetic reconnection is a universal phenomenon existing in the space. Energy conversion is one of the essential parts of reconnection discussed for decades. Positive energy conversion ( J · E ′ > 0) is usually regarded as the sign of electron diffusion region (EDR), while the negative one ( J · E ′ < 0) turns out to gather in the outer EDR. Here we report the negative J · E ′ appearing in the inflow edge of the inner EDR, based on Magnetospheric Multiscale mission observations and particle‐in‐cell simulations. Both observations and simulations verify that this negative J · E ′ is mainly contributed from the electron pressure tensor term in generalized Ohm's law. The energy loss of electrons plays the dominant effect in the electron pressure tensor, and this energy decline is caused by the electric field which is induced by the decreasing magnetic field. Our results provide significant insights to expand the understanding of the reconnection regimes. Plain Language Summary: In interplanetary space and other space environments, magnetic reconnection can be detected through spacecraft observations. It affects the energy conversion between the fields and the plasmas. The positive energy conversion in the reconnection usually describes the process in that energy is transformed from the magnetic field to the particles. The negative one, however, represents the inverse form. With the help of satellite data, we find negative energy conversion in the inflow edge of the center site of magnetic reconnection (i.e., the inner electron diffusion region). We also perform kinetic simulations to verify the satellite observation results. These two results have well corresponded to a certain extent. We make further investigation on the simulation data to reveal the physical mechanism. It is found that electrons' energy has decreased in the inflow edge due to the electric field formed by the decreasing magnetic field in the inflow region. Such decline of the electrons' energy causes the change of electron pressure tensor. Our study may promote a more profound understanding of energy conversion during magnetic reconnection. Key Points: Negative energy conversion ( J · E ′ < 0) can appear in the inflow edge of the inner EDR during tail magnetic reconnection Both simulations and observations confirm that the negative energy conversion closely connects with the electron pressure tensor term The electric field induced by the decreasing magnetic field causes the electron velocity decline and negative energy conversion